Integrated Land Degradation Assessment through Geographic Information Systems and Soil Biophysical Evaluation in Kalibeluk Village, Batang Regency - Farchan Mushaf Al Ramadhani; Muhammad Naoval Haris; Muhammad Akmal Faza (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2026)
Land degradation is a major environmental issue that reduces soil productivity and impairs ecological functions. Kalibeluk Village, Batang Regency, has diverse biophysical characteristics that may result in varying levels of land degradation. This study assessed land degradation potential and the corresponding degradation status in Kalibeluk Village, using GIS-based spatial analysis supported by field verification and laboratory assessment. Spatial analysis was conducted using soil type, slope gradient, rainfall, and land use parameters through an overlay technique to determine land degradation potential. Field verification and laboratory analyses were subsequently performed for each Land Mapping Unit (LMU) to evaluate land degradation status based on Government Regulation of the Republic of Indonesia Number 150 of 2000 and Regulation of the State Minister of Environment Number 07 of 2006. The results classified land degradation potential into three categories: low (71.481 ha; 39.8%), moderate (104.167 ha; 57.9%), and high (4.137 ha; 2.3%). Evaluation of land degradation status indicated that LMUs with low and moderate degradation potential were categorized as Slightly Degraded (R.I), whereas LMUs with high degradation potential were categorized as Moderately Degraded (R.II). The main limiting factors were soil fraction composition, water permeability, redox conditions, and surface rockiness. The findings demonstrate that GIS is an effective tool for identifying land degradation levels and supporting land management planning. Recommended rehabilitation measures include agroforestry, cover crops, terracing, the application of organic matter and soil amendments, and conservation drainage systems to improve soil quality and reduce land degradation risks sustainably.